Education and Society: Towards a New Decolonial Epistemological Turn - Cruz Picón, Pablo Emilio (2024)
The objective of this essay is to redefine the value of the approaches of Latin American theorists, such as Boaventura, Dussel, Freire, Grosfoguel, Zea and Zuleta, among other authors, who advocate a decolonial education based on criticality, cultural diversity, own knowledge, emancipation, and liberation, among other features. For this reason, the analysis was based on a qualitative hermeneutic-analytical approach. Among the main contributions, it is determined that the construction of a decolonial pedagogy is obtained from a polynomial epistemic-humanist-ethical alliance: the recognition of the other, interculturality, critical-emancipatory pedagogy, and the validity of ancestral knowledge. It is concluded that the decolonial turn and epistemological decolonization not only outlines theoretical perspectives, but also a possible cognitive pragmatism that guides epistemic praxis to a sociopolitical terrain, where human beings recognize their history and place in the world.